Analysis of Policy Factors of Human Resources in Company Performance - Awaliyah, Iysatul Hazar; Rozikin, Opik (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2021)
This study, conducted at PT. Pos Indonesia Banjar Branch, focuses on HR policies regarding recruitment, selection, placement as well as compensation by using a qualitative approach with a case study method. The data were taken from interviews with the HR Manager as well as the Head of the Post Office, observations, and documentation. The results showed that the recruitment policy implemented by PT. Pos Indonesia Banjar branches are (1) Opening 50% of job vacancies for apprentice students, 30% open to the public through advertising and 20% open based on recommendations from internal employees. (2) The process of placing employees is based on the selection process and the competence of employees. (3) Compensation policies, that have been implemented "well", meet the eligibility requirements and the Regional Minimum Wage (UMR) standard. In conclusion, PT. Pos Indonesia Banjar Branch needs to emphasize policies to human resources in order to maintain good company performance.